We have to solve the simultaneous equation

y^2 - 4xy + 4y = 1 ...(1)

3x^2 - 2xy = 1 ...(2)

We see that it is not possible to isolate x in terms of y or y in terms of x using any of the equations.

In (1) we get...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve the simultaneous equation

y^2 - 4xy + 4y = 1 ...(1)

3x^2 - 2xy = 1 ...(2)

We see that it is not possible to isolate x in terms of y or y in terms of x using any of the equations.

In (1) we get y = 1/(y - 4x + 4)

In (2) we get x = 1/(3x - 2y)

As this is the case, we cannot the solve the system of simultaneous equations. Using a random solution of (1 , 1), we do get both

y^2 - 4xy + 4y = 1 and 3x^2 - 2xy = 1

**The required solution of the equations is (1, 1)**